Different levels of induction of RecA protein in E. coli (PQ 10) after treatment with two related carcinogens. - Salles, B (1983)
By means of an immunoradiometric assay the induction of protein RecA in E. coli PQ 10 was measured after treatment by two related carcinogens. On an adduct basis N-Acetoxy-N-2-acetylaminofluorene was shown to induce the protein RecA at a similar level as U.V. On the other hand, N-hydroxy-N-2-aminofluorene shows only a poor induction capacity of the RecA protein. The difference in the SOS inducing potential of the aminofluorene and acetylaminofluorene adducts is discussed in relation to the major difference in the local conformational change the two adducts induce in DNA.